The Last Two Remaining Populations of the Critically Endangered Estuarine Pipefish Are Inbred and Not Genetically Distinct - Weiss, Sven-Erick; Emami-Khoyi, Arsalan; Kaiser, Horst; Cowley, Paul D.; James, Nicola C.; Jansen van Vuuren, Bettine; Whitfield, Alan K.; Teske, Peter R. (Frontiers in Marine Science, 2022)
The critically endangered estuarine pipefish, Syngnathus watermeyeri, is one of Africa’s rarest fish species and currently faces a significant risk of extinction. A combination of anthropogenic and natural factors threaten submerged macrophyte beds in the two South African estuaries (Bushmans and Kariega) in which the species’ only two known remaining populations reside. Here, we genotyped 34 pipefish from both populations using genome-wide data to determine whether the two estuaries harbour distinct genetic diversity, such that translocating individuals between them might improve the genetic health of both. Our results show that both populations are highly inbred, and no statistically significant genetic structure was found between them. Moreover, individuals both within and between estuaries were very closely related to each other. These results indicate that the remaining populations of the estuarine pipefish suffer from the adverse genetic effects of small population sizes. Even though recent surveys have estimated population sizes in the order of thousands of individuals, these may fluctuate considerably. Although the translocation of genetically similar individuals between habitats will not increase local genetic diversity, the creation of additional populations across the species’ historical range may be a suitable conservation strategy to prevent further loss of genetic diversity, and to minimise the overall extinction risk posed by environmental stochasticity.